Simplicius on the planets and their motions : in defense of a heresy - Bowen, Alan C. (Philosophia Antiqua, 2013)
Though the digression closing Simplicius' commentary on Aristotle's De caelo 2.12 has long been misread as a history of early Greek planetary theory, it is in fact a creative reading of Aristotle to maintain the authority of the De caelo as a sacred text in Late Platonism and to refute the polemic mounted by the Christian, John Philoponus. This book shows that the critical question forced on Simplicius was whether his school's acceptance of Ptolemy's planetary hypotheses entailed a rejection of Aristotle's argument that the heavens are made of a special matter that moves by nature in a circle about the center of the cosmos and, thus, a repudiation of the thesis that the cosmos is uncreated and everlasting.